ESL undergraduates' perception of plagiarism in academic writing - Zangenehmadar, Samaneh; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2014)
The purpose of this study is to investigate Malaysian undergraduates’ perception of plagiarism and university policies on plagiarism detection and prevention. The study also aims to identify the factors contributing to students’ plagiarism. Data were collected through a questionnaire distributed among undergraduates of different disciplines at a local public university. Results indicated that the students had quite good knowledge about the concept of plagiarism, its various forms, and university plagiarism policies. Most of the students mentioned the ease of copying and pasting from the Internet sources and getting a higher score as contributing factors to commit plagiarism. The study offers a significant contribution in the area of plagiarism prevention. Although students have generally good knowledge of plagiarism, the results of the study may provide further evidence that students’ knowledge of plagiarism need to be improved, and lecturers need to understand the causes of students’ plagiarism. The study suggests that educators need to provide more information on plagiarism, referencing rules and paraphrasing in academic writing to reduce students’ plagiarism.